2020
DOI: 10.3390/antiox9050414
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Hypoxia and Placental Oxidative Stress: Insights from Animal Models to Clinical Evidences

Abstract: Hypoxia is a common form of intrauterine stress characterized by exposure to low oxygen concentrations. Gestational hypoxia is associated with the generation of reactive oxygen species. Increase in oxidative stress is responsible for damage to proteins, lipids and DNA with consequent impairment of normal cellular functions. The purpose of this review is to propose a summary of preclinical and clinical evidences designed to outline the correlation between fetal hypoxia and oxidative stress. The results of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 133 publications
(137 reference statements)
0
23
0
1
Order By: Relevance
“…Here, we demonstrated that supplementation of WSD-fed mothers with resveratrol reduced fetal hepatic oxidative stress, decreased periportal collagen deposition, and decreased ACTA2 + and ACTA2 and TIMP1 double-positive portal triad HSCs/myofibroblasts to levels comparable to CD fetuses. Activation of oxidative stress in WSD-exposed fetuses may result from decreased umbilical artery oxygenation ( 22 ) and impaired placental function ( 22 , 62 , 63 ). Importantly, we found that SHG area correlated positively with markers of fetal hypoxemia, suggesting that fetal stress and hypoxemia might be drivers of liver fibrosis in utero.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that supplementation of WSD-fed mothers with resveratrol reduced fetal hepatic oxidative stress, decreased periportal collagen deposition, and decreased ACTA2 + and ACTA2 and TIMP1 double-positive portal triad HSCs/myofibroblasts to levels comparable to CD fetuses. Activation of oxidative stress in WSD-exposed fetuses may result from decreased umbilical artery oxygenation ( 22 ) and impaired placental function ( 22 , 62 , 63 ). Importantly, we found that SHG area correlated positively with markers of fetal hypoxemia, suggesting that fetal stress and hypoxemia might be drivers of liver fibrosis in utero.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a common feature of preeclampsia and FGR [ 17 , 174 ]. Placental hypoxia is long believed to induce oxidative stress by stimulating ROS generation in mitochondria and other compartments of uteroplacental cells, leading to placental dysfunction and subsequent development of preeclampsia and FGR [ 17 , 18 , 174 ]. The placenta is a metabolically active organ and has a high nutrient and energy demand.…”
Section: Mitochondrial Ros and Preeclampsia/fgrmentioning
confidence: 99%
“…It is now recognized that both preeclampsia and FGR originate from the placenta due to uteroplacental dysfunction conferred by gestational hypoxia [ 1 , 12 , 13 , 14 , 15 ]. Gestational hypoxia is associated with overproduction in reactive oxygen species (ROS) in the placenta, leading to oxidative stress [ 12 , 16 , 17 , 18 ]. ROS can be beneficial or deleterious, depending on their levels in cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal hypoxia also leads to increased placental oxidative stress and decreased mitochondrial respiration and mitochondrial fusion, which may lead to disorders of placental function and fetal development ( Ganguly et al, 2021 ). Increased oxidative stress also leads to damage to proteins, lipids and DNA, which disrupts normal cellular function ( Silvestro et al, 2020 ). Rapid re-oxygenation after hypoxia can disrupt the fetal blood-brain barrier by producing ROS, thereby amplifying the effects of molecules in fetal blood on the brain ( Piesova and Mach, 2020 ).…”
Section: Possible Mechanisms Underlying the Neurological Disorders Caused By Prenatal Hypoxiamentioning
confidence: 99%